2021
DOI: 10.3390/ijms22189739
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Investigations on the G Protein Dependent Signaling Pathways of Histamine Receptors

Abstract: G protein activation represents an early key event in the complex GPCR signal transduction process and is usually studied by label-dependent methods targeting specific molecular events. However, the constrained environment of such “invasive” techniques could interfere with biological processes. Although histamine receptors (HRs) represent (evolving) drug targets, their signal transduction is not fully understood. To address this issue, we established a non-invasive dynamic mass redistribution (DMR) assay for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 112 publications
(262 reference statements)
0
10
0
1
Order By: Relevance
“…The Gβγ subunit of activated Gα i proteins is a potential candidate since it has been shown to directly trigger specific exchange factors which in turn activate the Rho GTPase Cdc42 leading to actin remodeling (Meili and Firtel, 2003;Ueda et al, 2008;Yan et al, 2012). In support of this hypothesis, a recent study shows that inhibition of the βγ-arm of the histamine h4R signaling pathway decreases DMR responses (Seibel-Ehlert et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Gβγ subunit of activated Gα i proteins is a potential candidate since it has been shown to directly trigger specific exchange factors which in turn activate the Rho GTPase Cdc42 leading to actin remodeling (Meili and Firtel, 2003;Ueda et al, 2008;Yan et al, 2012). In support of this hypothesis, a recent study shows that inhibition of the βγ-arm of the histamine h4R signaling pathway decreases DMR responses (Seibel-Ehlert et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Typically, receptor modulators will produce either a positive DMR response, where movement of cellular components into a focal plane within ∼150 nm of the substrate increases the wavelength of the reflected light or, conversely, a negative DMR response where movement of cellular component outside the focal plane decreases the wavelength of the reflected light. Numerous GPCRs have been evaluated in label free platforms such as the Epic ® including the metabotropic acetylcholine receptors ( Dodgson et al, 2009 ; Kebig et al, 2009 ; Lee, 2009 ; Schroder et al, 2010 ; Schroder et al, 2011 ; Schrage et al, 2013 ), dopamine receptors ( Lee, 2009 ), cannabinoid receptors ( Schroder et al, 2010 ; Codd et al, 2011 ), prostaglandin receptors ( Schroder et al, 2010 ), free fatty acid receptor ( Schroder et al, 2010 ; Schmidt et al, 2011 ), adrenergic receptors ( Schroder et al, 2010 ; Ferrie et al, 2014 ; Grundmann et al, 2018 ), γ-aminobutyric acid receptors ( Klein et al, 2016 ), the nociceptin/orphanin FQ peptide receptor ( Malfacini et al, 2018 ), the neuropeptide S receptor ( Ruzza et al, 2018 ), the uracil nucleotide/cysteinyl leukotriene receptor ( Grundmann et al, 2018 ), histamine receptors ( Seibel-Ehlert et al, 2021 ), the urotensin receptor ( Lee et al, 2014 ) and opioid receptors ( Codd et al, 2011 ; Morse et al, 2011 ). It has now become clear that both the cellular context and the type of coupling can directly influence the kinetics (positive or negative DMR) of a modulator in such a cell-based assay ( Schroder et al, 2010 ; Schroder et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Os efeitos biológicos da histamina são mediados pela sua ligação a quatro subtipos de recetores: os histamine receptors (HR)1, HR2, HR3 e HR4, que pertencem à família dos recetores acoplados à proteína G (G protein--coupled receptors, GPCRs) (5,6,11,12).…”
Section: Tipos De Recetores Histaminérgicosunclassified
“…This is also being discussed for D 2 -like receptors and is the subject of current research because an improved side effect profile is desirable especially in diseases such as PD and schizophrenia 35 . Just recently, detailed studies using histamine receptors and the human sweet taste receptor showed that G protein-dependent signalling pathways and G protein biased ligands can be studied with DMR 36 , 37 . Another strength of the DMR technique is its outstanding sensitivity, allowing the study of GPCRs at endogenous expression levels 30 .…”
Section: Introductionmentioning
confidence: 99%